2020
DOI: 10.1109/mc.2020.2998235
|View full text |Cite
|
Sign up to set email alerts
|

Open Source Research Software

Abstract: ware is a central asset for development activities. For good scientific practice, the resulting research software should be open source. Established open source software licenses provide sufficient options for granting permissions such that it should be the rare exception to keep research software closed. Proper engineering is required for obtaining reusable and sustainable research software. This way, software engineering methods may improve research in other disciplines. However, research in software enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
(3 reference statements)
0
17
0
Order By: Relevance
“…Yet, this software is critical for correctly carrying out research that involves modeling biological structures, or simulating data on evolution, and so forth [4]. These software artifacts are also needed by other researchers who attempt to build upon prior work; hence the need for making software open source [16].…”
Section: Design Risks In Computational Sciencementioning
confidence: 99%
“…Yet, this software is critical for correctly carrying out research that involves modeling biological structures, or simulating data on evolution, and so forth [4]. These software artifacts are also needed by other researchers who attempt to build upon prior work; hence the need for making software open source [16].…”
Section: Design Risks In Computational Sciencementioning
confidence: 99%
“… Lack of suitable incentive systems : Contributions to research that are not traditional text-based products (i.e., papers or monographs) are still not sufficiently rewarded, or not rewarded at all, due to the missing implementation of mandatory software citation 20 , 24 – 32 , among other reasons. Interestingly, one third of research software repositories have a lifespan (defined as the time from the first time any code was uploaded to the last contribution) of less than one day (median: 15 days 11 ), indicating that many codes are only made available publicly for the publication in a journal (as increasingly encouraged or required by journals 33 and associated with higher impact 34 ) but are not maintained thereafter. Lack of awareness : Research software sustainability and its importance is lacking visibility as well as acceptance 35 – 38 , and research software engineering in its implementation as sustainable software development and software maintenance is not sufficiently supported, both in Germany and beyond 9 , 39 , 40 .…”
Section: Why Sustainable Research Software In the First Place?mentioning
confidence: 99%
“…Hasselbring et al . found that the adoption of FAIR principles is different between fields with an emphasis on reuse in computer science as opposed to a reproducibility focus in computational science 11 . Fehr et al .…”
Section: How To Decide Which Software To Sustain?mentioning
confidence: 99%
See 1 more Smart Citation
“…For version control, tracking and reproducibility, the results are stored together with the setup files. Based on the results, other research might be launched and findings are published, preferably including the code contribution(Hasselbring et al, 2020).…”
mentioning
confidence: 99%